Reactivity to Social Stress in Subclinical Social Anxiety: Emotional Experience, Cognitive Appraisals, Behavior, and Physiology - Crişan, Liviu G.; Vulturar, Romana; Miclea, Mircea; Miu, Andrei C. (Frontiers in Psychiatry, 2016)
Recent research indicates that subclinical social anxiety is associated with dysfunctions at multiple psychological and biological levels, in a manner that seems reminiscent of social anxiety disorder (SAD). This study aimed to describe multidimensional responses to laboratory-induced social stress in an analog sample selected for social anxiety symptoms. State anxiety, cognitive biases related to negative social evaluation, speech anxiety behaviors and cortisol reactivity were assessed in the Trier Social Stress Test (TSST). Results showed that social anxiety symptoms were associated with increased state anxiety, biased appraisals related to the probability and cost of negative social evaluations, behavioral changes in facial expression that were consistent with speech anxiety, and lower cortisol reactivity. In addition, multiple interrelations between responses in the TSST were found, with positive associations between subjective experience, cognitive appraisals and observable behavior, as well as negative associations between each of the former two types of response and cortisol reactivity. These results show that, in response to social stressors, subclinical social anxiety is associated with significant changes in emotional experience, cognitive appraisals, behaviors and physiology that could parallel those previously found in SAD samples.